Edukasi Kesehatan: Meningkatkan Pengetahuan Dan Sikap Ibu Terhadap Kelengkapan Imunisasi Dasar Di Desa Suka Raya Kecamatan Pancur Batu - fani, Tifani Hadi Tri Wahyuni (STIKES Columbia Asia Medan, 2025)
The coverage of complete basic immunization remains a serious public health concern, particularly in rural areas such as Suka Raya Village, Pancur Batu Subdistrict, where only 26.2% of infants have received full basic immunizations. Low maternal knowledge and negative attitudes are among the primary barriers contributing to this issue. This community service activity was designed to increase the knowledge and attitudes of mothers regarding the importance of complete basic immunization through structured health education. The activity involved 42 mothers with infants aged 9–12 months and was conducted in July 2025 at the Suka Raya Village Hall. The method consisted of interactive lectures, distribution of educational leaflets, and direct discussions facilitated by health educators. Pre- and post-intervention questionnaires were used to assess changes in knowledge and attitudes. The results showed a significant improvement: mothers with good knowledge increased from 47.6% to 85.7%, and those with positive attitudes increased from 42.9% to 83.3%. The findings support that community-based health education interventions can effectively enhance maternal understanding and behavioral intentions toward completing their children's immunization schedules. It is recommended that similar educational activities be regularly implemented and supported by local health institutions and cadres. This initiative demonstrates the importance of empowering mothers at the grassroots level to improve child health outcomes.